Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

For discussing anything related to physics, biology, chemistry, mathematics, and their practical applications.

Moderator: Flannel Jesus

Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ed3 » Tue Jun 13, 2017 9:32 pm

The Excluded Middle is: (Not (Not A)) → A. If this is not the case then is it true that the following proposition is also true: (A ʌ -A)?

I am working on a post which has Brouwer /Constructivism as major subjects.

Thanks Ed
"Albert! Stop telling God what to do." - Niels Bohr
Ed3
Thinker
 
Posts: 875
Joined: Sun Oct 31, 2004 2:56 pm
Location: Lakeville MN USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Carleas » Tue Jun 13, 2017 11:05 pm

As I understand your question, it's \( \neg ( \, \neg (\neg A) \rightarrow A) \overset{?}{\rightarrow} (A \land \neg A) \)

i.e., if it's not the case that [not not A implies A], then [A and not A]. Is that right? I will need to think more about the answer to the question, I just wanted to make sure I have it right before I get going.
User Control Panel > Board preference > Edit display options > Display signatures: No.
Carleas
Magister Ludi
 
Posts: 5444
Joined: Wed Feb 02, 2005 8:10 pm
Location: Washington DC, USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby James S Saint » Wed Jun 14, 2017 1:09 am

Ed3 wrote:The Excluded Middle is: (Not (Not A)) → A. If this is not the case then is it true that the following proposition is also true: (A ʌ -A)?

I am working on a post which has Brouwer /Constructivism as major subjects.

Thanks Ed

The symbol "ʌ" means "and also".

So the question is: If a middle is allowed between A and not-A, then can one have both A and also not-A at the same time?

And the answer is that it is anyone's guess because if logic doesn't apply, then there are no consistent rules (because consistency in language is what logic is).

The new possible cases would be; that both A and also not-A exited, that neither A nor not-A existed, or that neither A nor not-A applied to the situation at all (such as the presence of an nonsensical statement; e.g. "this statement is false"). Take your pick
Last edited by James S Saint on Wed Jun 14, 2017 4:55 am, edited 1 time in total.
Clarify, Verify, Instill, and Reinforce the Perception of Hopes and Threats unto Anentropic Harmony :)
Else
From THIS age of sleep, Homo-sapien shall never awake.

The Wise gather together to help one another in EVERY aspect of living.

You are always more insecure than you think, just not by what you think.
The only absolute certainty is formed by the absolute lack of alternatives.
It is not merely "do what works", but "to accomplish what purpose in what time frame at what cost".
As long as the authority is secretive, the population will be subjugated.

Amid the lack of certainty, put faith in the wiser to believe.
Devil's Motto: Make it look good, safe, innocent, and wise.. until it is too late to choose otherwise.

The Real God ≡ The reason/cause for the Universe being what it is = "The situation cannot be what it is and also remain as it is".
.
James S Saint
ILP Legend
 
Posts: 25785
Joined: Sun Apr 18, 2010 8:05 pm

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ed3 » Wed Jun 14, 2017 3:08 am

Hi Carleas,

Yes. You understand the question properly, and I am eager to hear your response.

Thanks Ed
"Albert! Stop telling God what to do." - Niels Bohr
Ed3
Thinker
 
Posts: 875
Joined: Sun Oct 31, 2004 2:56 pm
Location: Lakeville MN USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ed3 » Wed Jun 14, 2017 3:29 am

Hi James,

I understand the symbol ˄ to mean the word "and" however your interpretation is perfectly suitable in my opinion. Additionally I have some of the same intuitive feelings that you have.

However, A ˄ -A can be used to prove anything, whereas simply renouncing the excluded middle, just makes mathematics more difficult rather than pointless.

In any case I would like to see a rigorous evaluation.

Thanks Ed
"Albert! Stop telling God what to do." - Niels Bohr
Ed3
Thinker
 
Posts: 875
Joined: Sun Oct 31, 2004 2:56 pm
Location: Lakeville MN USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ed3 » Wed Jun 14, 2017 4:12 am

Hi Carleas,

I'm sorry!!! I did screw up the representation of my question.

I should have written – (NOT (NOT A) → A) imply (A Ʌ -A)

It appears that you have written the correct form.

Apologies - Ed
"Albert! Stop telling God what to do." - Niels Bohr
Ed3
Thinker
 
Posts: 875
Joined: Sun Oct 31, 2004 2:56 pm
Location: Lakeville MN USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby James S Saint » Wed Jun 14, 2017 4:54 am

Ed3 wrote:Hi Carleas,

I'm sorry!!! I did screw up the representation of my question.

I should have written – (NOT (NOT A) → A) imply (A Ʌ -A)

It appears that you have written the correct form.

Apologies - Ed

Are you sure about that?

Your OP said what Carleas said, but different than the Title. The title needs another "Not" in front.

Your new statement doesn't seem to say what you intended.
    If ~~A → A (which is does) then A and also ~A ???

You need "If ~~~A → A ..."
Clarify, Verify, Instill, and Reinforce the Perception of Hopes and Threats unto Anentropic Harmony :)
Else
From THIS age of sleep, Homo-sapien shall never awake.

The Wise gather together to help one another in EVERY aspect of living.

You are always more insecure than you think, just not by what you think.
The only absolute certainty is formed by the absolute lack of alternatives.
It is not merely "do what works", but "to accomplish what purpose in what time frame at what cost".
As long as the authority is secretive, the population will be subjugated.

Amid the lack of certainty, put faith in the wiser to believe.
Devil's Motto: Make it look good, safe, innocent, and wise.. until it is too late to choose otherwise.

The Real God ≡ The reason/cause for the Universe being what it is = "The situation cannot be what it is and also remain as it is".
.
James S Saint
ILP Legend
 
Posts: 25785
Joined: Sun Apr 18, 2010 8:05 pm

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby James S Saint » Wed Jun 14, 2017 7:15 am

I'm sure that you need something different because this seems too simple. The constructionist requires that the conclusion object be constructed. My question is how much of the rest are you allowed to assume, because it takes almost nothing to construct the (A ^ ~A) from the "~~~A → A".

~~A → A, LEM

| (~(~(~A)) → A) → (~A ^ A), hypothesis
|| (~~~A → A) → (~A ^ A)
| (~A → A) → (~A ^ A)
|
|| ~A, given
|| A ^ A, given
|| ~A → A, given hypothesis condition
| ~A ^ A, concluded hypothesis equivalent condition

(~(~(~A)) → A) → (~A ^ A)
Last edited by James S Saint on Wed Jun 14, 2017 2:51 pm, edited 1 time in total.
Clarify, Verify, Instill, and Reinforce the Perception of Hopes and Threats unto Anentropic Harmony :)
Else
From THIS age of sleep, Homo-sapien shall never awake.

The Wise gather together to help one another in EVERY aspect of living.

You are always more insecure than you think, just not by what you think.
The only absolute certainty is formed by the absolute lack of alternatives.
It is not merely "do what works", but "to accomplish what purpose in what time frame at what cost".
As long as the authority is secretive, the population will be subjugated.

Amid the lack of certainty, put faith in the wiser to believe.
Devil's Motto: Make it look good, safe, innocent, and wise.. until it is too late to choose otherwise.

The Real God ≡ The reason/cause for the Universe being what it is = "The situation cannot be what it is and also remain as it is".
.
James S Saint
ILP Legend
 
Posts: 25785
Joined: Sun Apr 18, 2010 8:05 pm

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ed3 » Wed Jun 14, 2017 1:14 pm

Hi James,

I can not keep up with the pace at which you post. This is a response to your second to last post.

I use the “–” sign and “NOT” interchangeably. (I wrote it the way that I did because I wanted to emphasize that I was talking about the Law of the Excluded Middle).

What I really screwed up, in the title, was the use of the parenthesis. The final “)” belongs after the arrow and not after the first “)”.

What is amazing is that Carleas caught my mistake from the content of the article. Additionally he could have read the title and simply thought “the old man is nuts” and never read the article.

Thanks Ed

P.S. I hope the proposition is false (and I think that it is) because it would ruin not only my upcoming post but almost everything else.
"Albert! Stop telling God what to do." - Niels Bohr
Ed3
Thinker
 
Posts: 875
Joined: Sun Oct 31, 2004 2:56 pm
Location: Lakeville MN USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby James S Saint » Wed Jun 14, 2017 2:05 pm

Well sorry Ed, now you have lost me.

Your OP said this:
Carleas wrote:As I understand your question, it's \( \neg ( \, \neg (\neg A)) \rightarrow A) \overset{?}{\rightarrow} (A \land \neg A) \)

i.e., if it's not the case that [not not A implies A], then [A and not A].

But now you seem to be saying something else.
Ed3 wrote:The final “)” belongs after the arrow and not after the first “)”.

That edit would merely be;
\((\neg (\neg A) \rightarrow A) \overset{?}{\rightarrow} (A \land \neg A) \)
\((A \rightarrow A) \overset{?}{\rightarrow} (A \land \neg A) \)

Obviously that isn't true nor relevant. And I don't think that is what you wanted either. So n/m.
Clarify, Verify, Instill, and Reinforce the Perception of Hopes and Threats unto Anentropic Harmony :)
Else
From THIS age of sleep, Homo-sapien shall never awake.

The Wise gather together to help one another in EVERY aspect of living.

You are always more insecure than you think, just not by what you think.
The only absolute certainty is formed by the absolute lack of alternatives.
It is not merely "do what works", but "to accomplish what purpose in what time frame at what cost".
As long as the authority is secretive, the population will be subjugated.

Amid the lack of certainty, put faith in the wiser to believe.
Devil's Motto: Make it look good, safe, innocent, and wise.. until it is too late to choose otherwise.

The Real God ≡ The reason/cause for the Universe being what it is = "The situation cannot be what it is and also remain as it is".
.
James S Saint
ILP Legend
 
Posts: 25785
Joined: Sun Apr 18, 2010 8:05 pm

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Carleas » Wed Jun 14, 2017 2:36 pm

I actually got the parentheses wrong too, though my verbal expression seems to have gotten it right. I've fixed it above, and I think we could take out some more parentheses to make it clearer (assuming negation precedes implication in the order of operations for logical operators).
\( \neg ( \, \neg \neg A \rightarrow A) \overset{?}{\rightarrow} (A \land \neg A) \)

I think James is right that we don't know what follows from this, although I don't think it's in principle undecidable. Rather, the statement is ambiguous: the \(\neg\) operator is a binary-logic operator. If \( \neg ( \, \neg \neg A \rightarrow A) \), it seems there must be a third truth-value besides true or false, and it isn't clear what the truth table for \( \neg \) looks like with respect to those three values.

On the other hand, if \( \neg ( \, \neg \neg A \rightarrow A) \), it doesn't seem that \(A \land \neg A \) is necessarily problematic. As I learned it, the proof that any statement follows from a contradiction relies on the law of the excluded middle. If that law doesn't apply, and \(\neg\) doesn't apply the way we think it does, we might be saved.

For example, if we have a three valued logic with values True, False, and Unknown, it might be that while A can't be both True and False, it can be True and Unknown. Then if we define \(\neg\) such that \(\neg True \rightarrow (Unknown \lor False)\), there is no contradiction for \(A \land \neg A \): \(A\) can be both True and Unknown.

So, I think the original question is just ambiguous. If the truth table for \(\neg\) is violated, we need a new truth table, but it's possible to make one that makes your statement consistent.
User Control Panel > Board preference > Edit display options > Display signatures: No.
Carleas
Magister Ludi
 
Posts: 5444
Joined: Wed Feb 02, 2005 8:10 pm
Location: Washington DC, USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ed3 » Thu Jun 15, 2017 12:06 am

Hi James,

I meant to ask the following:

Does the negation of the Law of the Excluded imply (A and Not A)?

If it does then it would be a giant disaster for Constructivism. (You can go to Wiki and search for the Principle of Explosion to see a proof that for all propositions, Q, (A and not A) imply Q). But I think you already knew that.

Thanks Ed
Last edited by Ed3 on Thu Jun 15, 2017 12:16 am, edited 1 time in total.
"Albert! Stop telling God what to do." - Niels Bohr
Ed3
Thinker
 
Posts: 875
Joined: Sun Oct 31, 2004 2:56 pm
Location: Lakeville MN USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ed3 » Thu Jun 15, 2017 12:10 am

Hi Carleas,

I think that you are right to claim that we would be required to use a multi valued logic if we deny the Law of the Excluded Middle. In practice I, personally, think in terms of the three values that you laid out. I.e. True, False and Unknown.

However Gödel had a proof that in fact the logic has to be infinitely valued.

I am not sure how to proceed here. I know that in classical math and binary logic we need to have the Law of the Excluded Middle. However in constructive math (which has a number of practical uses) and multi valued logic we can deny the Law of the Excluded Middle.

I just don’t want the denial of the Excluded Middle to imply (A and Not A).

If a proof can be constructed, preferably not using the Law of the Excluded Middle (basically I don’t want a proof by contradiction) I am still interested.

A simple counter example might be OK. I know that some Constructivists will still allow Not (A and Not A)

Thanks Ed
"Albert! Stop telling God what to do." - Niels Bohr
Ed3
Thinker
 
Posts: 875
Joined: Sun Oct 31, 2004 2:56 pm
Location: Lakeville MN USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby James S Saint » Thu Jun 15, 2017 8:39 am

Ed3 wrote:Hi James,

I meant to ask the following:

Does the negation of the Law of the Excluded imply (A and Not A)?

If it does then it would be a giant disaster for Constructivism. (You can go to Wiki and search for the Principle of Explosion to see a proof that for all propositions, Q, (A and not A) imply Q). But I think you already knew that.

Thanks Ed

Frankly Ed, I think it is a nonsense question. It is like asking;
If the hypotenuse of a right triangle is not equal to the square root of the sum of the squares, does 5 - 3 = 4?

I don't see how the lack of a law (or an existence) can imply the existence of anything .. other than irrationality. So the "rational" answer to the question would be "No. The lack of the LEM does not imply .. anything".

But the way to find out in constructive logic/math is to spell out the construction of A → ~(~A) and see if it necessarily requires the LEM without which (A ^ ~A) is necessary. But what is the acceptable constructivist proof that A → ~(~A)?

IF (A → ~(~A)) → ~(A ^ ~A) then

By contradiction:
    IF ~(A ^ ~A) then (A ^ ~A) is invalid. -- the LEM
    But
    1.IF (A ^ ~A) then ((A ^ ~A) ^ ~(A ^ ~A)), subst of "A" with "(A ^ ~A)"
    2..Assuming (A ^ ~A),
    3..Then ~(A ^ ~A), via 1 & 2, the construction of the LEM.
    4..Thus (A ^ ~A) is not true, via 3, a direct self-contradiction of the assumption.

    Or Perhaps easier to read:
    IF the lack of the LEM is the case then the LEM exists, in which case the lack of the LEM is not the case.

That should be a constructivism proof of the LEM. That proof did not require the LEM as a principle in use. But the lack of the LEM did not demand (A ^ ~A), quite the opposite. The lack of the LEM demands the LEM -- ~(A ^ ~A).

    (A ^ ~A) → ~(A ^ ~A) → LEM

So again the answer is "No."
Clarify, Verify, Instill, and Reinforce the Perception of Hopes and Threats unto Anentropic Harmony :)
Else
From THIS age of sleep, Homo-sapien shall never awake.

The Wise gather together to help one another in EVERY aspect of living.

You are always more insecure than you think, just not by what you think.
The only absolute certainty is formed by the absolute lack of alternatives.
It is not merely "do what works", but "to accomplish what purpose in what time frame at what cost".
As long as the authority is secretive, the population will be subjugated.

Amid the lack of certainty, put faith in the wiser to believe.
Devil's Motto: Make it look good, safe, innocent, and wise.. until it is too late to choose otherwise.

The Real God ≡ The reason/cause for the Universe being what it is = "The situation cannot be what it is and also remain as it is".
.
James S Saint
ILP Legend
 
Posts: 25785
Joined: Sun Apr 18, 2010 8:05 pm

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Carleas » Thu Jun 15, 2017 2:46 pm

Ed, I take it you have a specific project on which you're working that requires denying the LEM, but where \(A \land \neg A \) would break something. But I wonder if it would really be so bad if \(A \land \neg A \). Without the LEM, I don't think the Principle of Explosion applies.

The proof for the PoE as I learned it goes like this:
1. \(A \land \neg A\)
2. \(A \)
3. \(A \lor B \)
4. \( \neg A\)
5. \(\therefore B\)

But that relies on the LEM: the 'or' in line 3 is eliminated by contradiction to prove B. If \( A \land \neg A \), we can't use \( \neg A\) that way. So even if \(\neg ( \neg \neg A \rightarrow A) \rightarrow (A \land \neg A) \), none of the usually nasty consequences seem to follow. Especially in this case, where we've explicitly denied that the negation of ~A implies A.

So, I'm not sure what follows from \(\neg ( \neg \neg A \rightarrow A) \) (because it seems to break the very logic required to answer that question), but at the same time if something seemingly nasty does follow, it probably isn't as nasty as it seems (because the logic it needs to have any consequence is broken).

Or is there a way to prove the PoE without using contradiction?
User Control Panel > Board preference > Edit display options > Display signatures: No.
Carleas
Magister Ludi
 
Posts: 5444
Joined: Wed Feb 02, 2005 8:10 pm
Location: Washington DC, USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ed3 » Thu Jun 15, 2017 5:07 pm

Hi James,

I will respond after I complete my upcoming post, because some of what you commented on is best dealt with in that post.

Ed
Last edited by Ed3 on Thu Jun 15, 2017 5:25 pm, edited 1 time in total.
"Albert! Stop telling God what to do." - Niels Bohr
Ed3
Thinker
 
Posts: 875
Joined: Sun Oct 31, 2004 2:56 pm
Location: Lakeville MN USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ed3 » Thu Jun 15, 2017 5:09 pm

Hi Carleas,

That was freaking brilliant.

Thanks Ed
"Albert! Stop telling God what to do." - Niels Bohr
Ed3
Thinker
 
Posts: 875
Joined: Sun Oct 31, 2004 2:56 pm
Location: Lakeville MN USA

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ecmandu » Thu Jun 15, 2017 11:11 pm

This is really a matter of "what is beyond?"

Then getting into the additional muck of what is beyond beyond?

So let's say there's a tree.

What is beyond that tree? If nothing, then nothing exists besides the tree (lack of tree), and there is no beyond, there is no possible negation, from which to discern tree from not tree, such as a sidewalk, which is not tree.

So there is both a tree and not a tree, not tree, is "beyond"

You always need a beyond to see something, and a beyond is always -something

So what is beyond beyond?

How can we see beyond, which we know is there, without something beyond that?

You have a couple options.

You see the beyond by virtue of the non beyond: I.e the tree, or, and this is correct, you see the beyond by virtue of the tree, the non tree beyond, and a third variable which is beyond both of them...

Think of it this way...

We see the tree, we see the stars, and beyond those stars, there is another beyond that allows us to see the first beyond.

Not only does this imply a and not a, it implies another not a that forces the first not a to be a middle.
Ecmandu
ILP Legend
 
Posts: 6831
Joined: Thu Dec 11, 2014 1:22 am

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Ecmandu » Thu Jun 15, 2017 11:59 pm

Another way to look at this is the river situation.

You can't stand in the same river twice.
Then how can we ever get to a river? How do we name them?

It is both a river and not a river.

The same is true of trees etc...

It is both a tree and not a tree.

You can't even look at the same "a" twice, it is both, it's identity and not its identity.

The middle of the a and not a is a balance of acuity...

Not too far or too close..

It is this middle, which allows us to observe identity...

Far from there being a law of no middle, the middle is required for identity.
Ecmandu
ILP Legend
 
Posts: 6831
Joined: Thu Dec 11, 2014 1:22 am

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Jakob » Fri Jun 16, 2017 3:48 pm

Since "A" >< "A", ""A"="A"" always begs the question, and dissecting its implications will result in ambiguity of terms.
This is how such flat logic works - actual statements are discovered through inconsistencies in the abstract.
The abstraction that is the law of identity doesn't apply to the real world, hence the open ended nature of formal logic.
Image
For behold, all acts of love and pleasure are my rituals
User avatar
Jakob
ILP Legend
 
Posts: 5715
Joined: Sun Sep 03, 2006 9:23 pm
Location: look at my suit

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Meno_ » Fri Jun 16, 2017 11:17 pm

But the law of the excluded middle has very important philosophical implication, therefore, so does the law of identity.

Existentialism has direct connections to the law of the excluded middle. The philosophy in that sense can derive the logic which underlies the existential argument. Historical inevitability reduces to that logic.
Meno_
Philosopher
 
Posts: 2617
Joined: Tue Dec 08, 2015 2:39 am

Re: Does the proposition – (Not (Not A)) → A imply (A ʌ -A)?

Postby Jakob » Tue Jun 20, 2017 11:33 pm

Meno_ wrote:But the law of the excluded middle has very important philosophical implication, therefore, so does the law of identity.

I opposed both, precisely because they have been the ruin of thought.
Neither applies to reality. Both are means to make something different than reality.

Existentialism has direct connections to the law of the excluded middle. The philosophy in that sense can derive the logic which underlies the existential argument. Historical inevitability reduces to that logic.

In real existence, all statements of true fact are subjective statements of states. And such statements will always contradict other occasions where they have been made.
Phenomena have not yet been allowed into logic. Aristotle was really, a really dry sheet of paper.
Image
For behold, all acts of love and pleasure are my rituals
User avatar
Jakob
ILP Legend
 
Posts: 5715
Joined: Sun Sep 03, 2006 9:23 pm
Location: look at my suit


Return to Science, Technology, and Math



Who is online

Users browsing this forum: No registered users